Moral Markets and Moral Managers Revisited - Smith, Jeffery D. (Journal of business ethics, 2005)
In the wake of recent corporate scandals, this paper examines the claim made by John Boatright that business ethics, as it is currently conceived, “rests on a mistake.” Ethics in business should not be achieved through managerial vision, discretion or responsibility; rather, ethics should shape the design of institutions that regulate business from the outside. What ethicists should advocate for, according to Boatright, are moral markets not moral managers. I explore the empirical and normative dimensions of his claim with special attention paid to the extent to which Boatright’s development of the economic theory of the firm supports his position. I conclude by suggesting some reasons why moral markets and moral management are compatible frameworks for corporate reform.